The The Influence of Environmental Concern on the Intention to Pay Green Zakat: An Integration of the Theory of Planned Behavior - Kemas Ammar Amany; Nur Afifah; Ilzar Daud; Heriyadi; Ahmadi (Al-Qalam Institue, 2026)
Zakat has role strategic in distribution wealth and empowerment social, as well as potential support the development agenda sustainable development (SDGs) through draft green zakat. Although its potential big, realization zakat collection in Indonesia is still low. This study aims to analyze influence environmental concern to intention pay green zakat with integrate Theory of Planned Behavior (TPB) framework. Through approach quantitative PLS-SEM on 222 respondents, this study tested variables Subjective norm, attitude, and perceived behavioral control. Research results show that subjective norms, attitudes, and perceptions behavioral control influential positive and significant to intention pay green zakat. Meanwhile, environmental concerns No influential direct to intention, but rather through mediation full (full mediation) by variables attitude and perceived behavioral control. This finding confirms that concern ecological zakat payer new will transform become intention real If supported by attitude positive and perception convenience access technical. In conclusion, the success green zakat in Indonesia is not only depends on awareness environment society, but also on the ability institution in build literacy sustainability as well as provide infrastructure inclusive services to reduce obstacle behavior muzaki.